Metacommunity structure of the helminths of the black-eared opossum Didelphis aurita in peri-urban, sylvatic and rural environments in south-eastern Brazil. Issue 6 (17th September 2018) - Costa-Neto, S.F.; Cardoso, T.S.; Boullosa, R.G.; Maldonado, A.; Gentile, R.
Abstract: Among the Brazilian marsupials, the species of the genus Didelphis are the most parasitized by helminths. This study aimed to describe the species composition and to analyse the helminth communities of the Atlantic Forest common opossum Didelphis aurita at infracommunity and component community levels using the Elements of Metacommunity Structure Analysis, considering peri-urban, sylvatic and rural environments in the state of Rio de Janeiro, Brazil. Seventy-three specimens of D. aurita were captured during the study. Fourteen species of helminths were collected: nine of the phylum Nematoda ( Trichuris minuta, Trichuris didelphis, Globocephalus marsupialis, Heterostrongylus heterostrongylus, Travassostrongylus orloffi, Viannaia hamata, Aspidodera raillieti, Cruzia tentaculata and Turgida turgida ); four of the phylum Platyhelminthes (three species of Trematoda, Duboisiella proloba, Brachylaima advena and Rhopalias coronatus, and one species of the class Cestoda); and one species of the phylum Acanthocephala ( Oligacanthorhynchus microcephalus ). More than 95% of the animals were infected with parasites. The most abundant parasite species were V. hamata, T. turgida, C. tentaculata and T. orloffi . The nematodes T. turgida, C. tentaculata and A. raillieti were the most dominant species in the three environments. The analysis of the metacommunity structure indicated a structured pattern as a function of the environmental gradient, but only when all localities were considered together. At the infracommunity and component community levels, quasi-nested and nested structures with stochastic species loss were observed, respectively. The results indicate that the settlement of helminth species in the opossums can be attributed to the heterogeneity among individual hosts in relation to their exposure to parasites and to extrinsic factors, which vary among habitats, considering a regional scale. On a local scale, the characteristics of this host species may promote homogenization among individual hosts in terms of their exposure to the helminths. This study constitutes a new host record for the species G. marsupialis and T. didelphis and represents a pioneering investigation of the helminth metacommunity of a Neotropical marsupial.